Benzodiazepines in the treatment of alcoholism. - Nutt,D; Adinoff,B; Linnoila,M (Recent Dev Alcohol, 1989)
This chapter comprises three sections that cover the main aspects of benzodiazepines and alcohol: (1) the basic pharmacology of benzodiazepines; (2) use of benzodiazepines in the treatment of withdrawal; and (3) the use of benzodiazepines in treating alcoholics. The basic studies suggest that a major site of action of alcohol may be the GABA/benzodiazepine receptor complex and that compensatory alterations in this complex may underly withdrawal. In the section on alcohol withdrawal, interactions between the GABA/benzodiazepine receptor complex, sympathetic nervous system, and hypothalamic-pituitary-adrenal axis are discussed. Use of benzodiazepines in the treatment of the alcohol withdrawal syndrome are reviewed, including the possibility that the benzodiazepines may prevent withdrawal-induced "kindling." Lastly, we review indications for, and efficacy of, benzodiazepines in long-term treatment of patients with alcoholism. Benzodiazepines are not indicated for the treatment of alcoholism. Furthermore, they have very few indications in alcoholics and their dependency-producing potency has to be appreciated when they are used in patients with alcoholism.